Cyber Religion As An Innovation In Teaching The Qur'an And Hadith To Improve Religious Literacy Skills Among Students At MAN Pinrang - Wildayanti, Wildayanti; Amin, Sitti Jamilah; Saleh, Muhammad (Intiqad: Jurnal Agama dan Pendidikan Islam, 2025)
The objective of this research is to examine the level of students’ religious literacy and explore how cyber religion contributes to its enhancement. The research employs a qualitative method with an exploratory case study approach. Data were collected through observation, interviews, and documentation. Primary data sources include students, Qur'an and Hadith subject teachers, the Vice Principal for Curriculum Affairs, and the Principal. Secondary data were gathered from students’ searches on websites, platforms, and social media. The findings reveal that students’ religious literacy is at a good level. Students not only understand religious teachings conceptually but also apply them in their daily lives. They make good use of technology to access religious information, demonstrate the ability to analyze and critically evaluate the information they encounter, and exhibit wisdom and tolerance in communication and in responding to differences.